The Interaction Between Intracellular Energy Metabolism and Signaling Pathways During Osteogenesis - Ye, Jiapeng; Xiao, Jirimutu; Wang, Jianwei; Ma, Yong; Zhang, Yafeng; Zhang, Qiang; Zhang, Zongrui; Yin, Heng (Frontiers in Molecular Biosciences, 2022)
Osteoblasts primarily mediate bone formation, maintain bone structure, and regulate bone mineralization, which plays an important role in bone remodeling. In the past decades, the roles of cytokines, signaling proteins, and transcription factors in osteoblasts have been widely studied. However, whether the energy metabolism of cells can be regulated by these factors to affect the differentiation and functioning of osteoblasts has not been explored in depth. In addition, the signaling and energy metabolism pathways are not independent but closely connected. Although energy metabolism is mediated by signaling pathways, some intermediates of energy metabolism can participate in protein post-translational modification. The content of intermediates, such as acetyl coenzyme A (acetyl CoA) and uridine diphosphate N-acetylglucosamine (UDP-N-acetylglucosamine), determines the degree of acetylation and glycosylation in terms of the availability of energy-producing substrates. The utilization of intracellular metabolic resources and cell survival, proliferation, and differentiation are all related to the integration of metabolic and signaling pathways. In this paper, the interaction between the energy metabolism pathway and osteogenic signaling pathway in osteoblasts and bone marrow mesenchymal stem cells (BMSCs) will be discussed.